A preliminary evaluation of treatment duration on the resurgence of destructive behavior. Issue 1 (7th December 2019) - Greer, Brian D.; Fisher, Wayne W.; Retzlaff, Billie J.; Fuhrman, Ashley M.
Abstract : Quantitative models of resurgence (e.g., Behavioral Momentum Theory, Resurgence as Choice) suggest that resurgence is partly a function of the duration of extinction exposure, with longer histories of extinction producing less resurgence. This prediction is supported by some laboratory research and has been partially supported by clinical translations that did not isolate the effects of extinction exposure prior to testing for resurgence. The degree to which different histories of extinction impact the likelihood of treatment relapse in therapeutic applications of differential reinforcement is of great interest to the clinical community, including insurance carriers and other financial providers. In the present study, we isolated the effects of extinction history for severe destructive behavior across 6 participants referred for treatment services and examined resurgence of destructive behavior when alternative reinforcement terminated. Our within‐subject evaluation showed no difference in the level of resurgence or persistence of destructive behavior following short and long exposures to differential reinforcement with extinction. We discuss our failure to replicate in relation to experimental‐design considerations for investigating this and other relapse phenomena in future research with clinical populations.